The Tonsils Revisited: Review of the Anatomical Localization and Histological Characteristics of the Tonsils of Domestic and Laboratory Animals - Christophe Casteleyn; Sofie Breugelmans; Paul Simoens; Wim Van den Broeck (Clinical and Developmental Immunology)
This paper gives an overview of the anatomical localization and histological characteristics of the tonsils that are present in ten conventional domestic animal species, including the sheep, goat, ox, pig, horse, dog, cat, rabbit, rat, and pigeon. Anatomical macrographs and histological images of the tonsils are shown. Six tonsils can be present in domestic animals, that is, the lingual, palatine, paraepiglottic, pharyngeal, and tubal tonsils and the tonsil of the soft palate. Only in the sheep and goat, all six tonsils are present. Proper tonsils are absent in the rat, and pigeon. In the rabbit, only the palatine tonsils can be noticed, whereas the pig does not present palatine tonsils. The paraepiglottic tonsils lack in the ox, horse, and dog. In addition, the dog and cat are devoid of the tubal tonsil and the tonsil of the soft palate.